PENGARUH PRODUKTIVITAS KARYAWAN, KEPUASAN KARYAWAN DAN TURN OVER TERHADAP KEUNGGULAN BERSAING PERUSAHAAN MELALUI KINERJA KARYAWAN - Rina Irawati (Adbis: Jurnal Administrasi dan Bisnis, 2018)
The ability of a company to maintain the competitiveness is a benchmark of the company's success. The higher the ability of the company, the greater the profits received by the company. Satisfaction, turnover rate, and employee productivity are important elements that must be considered by the company in order to continuously improve competitiveness through its performance. This study was conducted to test the direct and indirect influence between satisfaction, turnover, and employee productivity to competitive advantage in UD. Angger Malang by using path analysis. The number of respondents in this study are 85 peoples. The results show that employee productivity has the smallest direct influence on competitive advantage with path coefficient of 0.210. Employee satisfaction has the greatest direct impact on competitive advantage with path coefficient of 0.342. Employee productivity has the least direct effect on company performance with path coefficient of 0.194. Turnover has the greatest direct impact on company performance with a path coefficient of 0.411. Employee satisfaction has the least indirect effect on competitive advantage with path coefficient of 0.037. Employee productivity has the greatest indirect effect on competitive advantage with path coefficient of 0.078. These results can indicate that the firm's performance variables have not been able to mediate the relationship between employee productivity, job satisfaction, and turnover of the company's competitive advantage.